Analisis Pengaruh Persepsi Harga, Lokasi dan Brand Image melalui Minat Beli terhadap Keputusan Pembelian Properti Syariah di Wilayah Bekasi - Saputra, Guntur Ade; Hendayana, Yayan; Navanti, Dovina; Martinio, Joseph; Hadita, Hadita (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This research aims to analyze the influence of perceived price, location and brand image on purchasing decisions, both directly and through moderating variables of purchasing interest in purchasing sharia property in the Bekasi area. The research method uses a quantitative approach with path analysis tests to measure the relationship between variables. Data was collected through questionnaires filled out by respondents regarding company operations and marketing. The research results show that perceptions of price, location and brand image have a significant influence on purchasing decisions. Purchase interest acts as a mediator that strengthens the relationship between these variables in determining purchasing decisions. However, price perception does not have a direct influence on buying interest, while location shows a negative influence on buying interest. On the other hand, brand image has a significant and positive influence on purchasing decisions. In conclusion, pricing strategies, location and brand image are the keys to creating superior buying interest in determining sharia property purchasing decisions in the Bekasi area.